Efektivitas Penerapan Electronic Traffic Law Enforcement (ETLE) melalui Pengawasan CCTV dalam Penertiban Lalu Lintas di Jalan Balai Kota Medan - Olivia Bebby; Agung Suharyanto (Universitas Medan Area, 2025)
This study aims to evaluate the effectiveness of the Electronic Traffic Law Enforcement (ETLE) system through CCTV surveillance on Balai Kota Street, Medan City. The research focuses on how far ETLE contributes to improving traffic discipline while also identifying obstacles that hinder its implementation. A qualitative approach with a descriptive method was applied, using interviews, observations, and documentation as data collection techniques. Data were analyzed thematically by referring to Duncan’s theory of organizational effectiveness, which consists of three approaches: Goal Approach, which assesses effectiveness based on the achievement of objectives; System Approach, which evaluates the organization’s ability to acquire, manage, and maintain resources; and Strategic Constituencies Approach, which measures effectiveness based on the extent to which the needs of key stakeholders are satisfied. The findings indicate that ETLE has made a positive contribution by increasing public awareness and encouraging more disciplined road use. However, its effectiveness remains limited due to technical issues such as signal disruptions and poor CCTV image quality; administrative problems related to outdated vehicle ownership data; and low public awareness caused by insufficient socialization. Therefore, improving technical facilities, updating vehicle data, and enhancing public education are crucial for optimizing ETLE implementation.